On Stationary Probabilities of State-Dependent Markov Retrial Queue (Моделювання, керування та інформаційні технології, 2023)
In this paper, we consider the Markov model of a multiserver retrial queue with an input flow rate that depends on the number of calls in an orbit and with a limited number of retrials. We have obtained the conditions for the existence of the stationary regime and presented formulas for steady-state probabilities. Our approach is based on the approximation of the input model by the model with truncated state space.